HISTORICAL, FAUNISTIC AND ZOOGEOGRAPHICAL CHARACTERISTIC OF MAMMALS OF THE CAUCASUS - G. M. Abdurakhmanov; A. M. Batkhiev (Юг России: экология, развитие)
Abstract. Subject, theme, aim of the work. Caucasian mountainous country is the original biogeographic region with a large number of endemic species, including mammals. The aim of the work was to conduct a historical analysis of the development of a modern faunal zoogeographical structure of the Caucasus theriofauna.Methods. We used in the work the methods of paleogeographic, historical and faunal analysis of the causes and ways of modelling a modern structure of Caucasus theriofauna and distribution of kinds and faunal species of mammals on its territory. There was a detailed analysis of all the available literature on the history of nature and fauna formation of the Caucasus, habitats of mammals, and their modern zoogeographical structure. Such a methodological approach allows us to explain many features of modern zoogeographic Caucasus theriofauna, not amenable to scientific explanation from the perspective of modern geographical situation.Results. The conducted detailed analytical overview of the formation problem and the nature of the current state of the Caucasus theriofauna lets explain, in terms of genesis, in close connection with the history of the Caucasus nature formation, a way of formation as well as the structure of the current state of the zoogeographical Caucasus theriofauna and the difference between the faunal complexes of its individual parts. As a result, now a there is picture of reconstruction of the most probable path of becoming the mammalian fauna of the Caucasus since ancient times to the present day , influenced by the formation of the structure of high-altitude zone, and then the patterns of glaciation in the region.The area of the results application. The results are of considerable theoretical and practical importance as a basis for assessing the causes of faunal diversity of ecological-faunal systems of mammals and patterns of their genetic relationship to the specific landscape. Of particular importance are the results for the implementation of the objective zoogeographical zoning of the Caucasus, the identification and protection of endemics, rare and endangered species, acclimatization and re-acclimatization of mammals.Summary. It has been conducted the most comprehensive thematic overview of the stages of the Caucasus joint historical landscape development and its flora and fauna, many of which defined zoogeographical characteristics of the region and its relations with the surrounding areas, ways and means of protection, use and reproduction.